1998
DOI: 10.1128/iai.66.6.2691-2697.1998
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferiStimulates the Production of Interleukin-10 in Peripheral Blood Mononuclear Cells from Uninfected Humans and Rhesus Monkeys

Abstract: Heat-killed Borrelia burgdorferi spirochetes stimulate in vitro production of interleukin-10 (IL-10) at both mRNA and protein levels in peripheral blood mononuclear cells (PBMC) of uninfected rhesus monkeys. A concomitant down-modulation of IL-2 gene transcription was observed. Neither IL-4 nor gamma interferon gene expression was ostensibly affected by B. burgdorferispirochetes. These phenomena were observed regardless of whether the stimulating spirochetes belonged to the B. burgdorferisensu stricto, Borreli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…This inflammatory response thus requires prior exposure to B. burgdorferi. In contrast, peripheral blood mononuclear cells (PBMC) of naive rhesus macaques, or bone marrow macrophages of naive mice, are able to produce inflammatory cytokines, including IL-6, in response to lipoproteins or lipopeptides [14,30]. This apparent paradox may be explained in terms of the cellular composition of these cell compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inflammatory response thus requires prior exposure to B. burgdorferi. In contrast, peripheral blood mononuclear cells (PBMC) of naive rhesus macaques, or bone marrow macrophages of naive mice, are able to produce inflammatory cytokines, including IL-6, in response to lipoproteins or lipopeptides [14,30]. This apparent paradox may be explained in terms of the cellular composition of these cell compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Mice (four to five per group) were subcutaneously inoculated in the cervical region with live lowpassage B. burgdorferi (4×10 6 spirochetes/mouse) of the JD1 strain. Spirochetes were cultivated as described previously [30].…”
Section: Animals and Infectionsmentioning
confidence: 99%
“…It has been shown that B.b. induces the secretion of IL-10 in mononuclear cells (54), and the clearance of B.b. in IL-10 deficient mice is 10 times higher than in their wild-type littermates (55).…”
Section: Inactivation Of Effector Mechanismsmentioning
confidence: 99%
“…We further hypothesized that the key B. burgdorferi effector molecules leading to reactive gliosis were lipoproteins. Spirochetal lipoproteins are potent immunopotentiators [21][22][23][24][25][26][27][28][29]. As many as 150 open reading frames potentially encoding lipoproteins have been identified in the genome of B. burgdorferi [30,31].…”
Section: Introductionmentioning
confidence: 99%